The Effect of Website Quality, Sales Promotion and Social Media on Purchase Decisions on Lazada E-Commerce Sites - Tia Amelia Dini Nadia; Rahmad Wijaya; Dewi Nurjannah (Universitas Muhammadiyah Malang, 2021)
This study aims to determine the effect of website quality, sales promotion, and social media on purchasing decisions on the Lazada e-commerce site. This type of research is explanatory research with a quantitative approach. The sampling technique used is accidental sampling. The number of samples used was 100 respondents. Respondents in this study were all Lazada consumers who had purchased at Lazada during the last 1 year. The source of data in this study is primary data obtained from distributing questionnaires through Lazada's social media. The data analysis technique used is multiple linear regression analysis. Data processing was performed with SPSS 26.0. The results of this study indicate that partially website quality, sales promotion, and social media have a positive and significant effect on purchasing decisions on the Lazada site. The dominant variable in influencing purchasing decisions is website quality.